Study on the impact behaviour of concrete-encased CFST box members. (1st November 2019) - Hou, Chuan-Chuan; Han, Lin-Hai; Wang, Fa-Cheng; Hu, Chang-Ming
Highlights: Experimental study on 20 concrete-encased CFST box specimens under drop hammer impact. Analysis of the measured failure modes, impact force and mid-span deflection. Numerical study on the composite effects of RC and CFST components under impact. Abstract: This paper presents an experimental and numerical study on the lateral impact behaviour of concrete-encased concrete-filled steel tubular (CFST) box beams and columns. A total of 20 specimens with test parameters including the impact energy, the boundary conditions and the axial load level, are tested under a drop hammer impact apparatus. The experimental results, namely the failure modes, the time-history of the impact force and mid-span deflection, as well as the whole impact process, are analysed. It shows that the specimens fail in a shear-flexural pattern under the impact. The major features of the impact force and mid-span deflection curves are summarised and analysed. The influence of test parameters on the impact behaviour of the specimens, namely the peak value of the impact force, the impact duration and the residual mid-span deflection, are also discussed. A finite element analysis (FEA) model is established to investigate the composite effects between the RC and CFST components. The analysis shows that the RC component is the major impact resistance component in the structure. The CFST components, on the other hand, is well protected by the RC component and do not experience severe damage. The composite effects make the structure safer under impact loading and easier to be restored after impact.